Cell-Membrane-Localizing, Two-Photon Probe for Ratiometric Imaging of γ-Glutamyl Transpeptidase in Cancerous Cells and Tissues - Reo, Ye Jin; Dai, Mingchong; Yang, Yun Jae; Ahn, Kyo Han (Analytical chemistry (Washington), 2020)
γ-Glutamyl transpeptidase (GGT), a cell surface-bound protease, is associated with various diseases including cancer. The detection of the enzyme activity is an important subject, leading to about 40 activatable fluorescent probes so far. All of them, however, lack the membrane-localizing ability, raising a reliability issue in the quantitative analysis. Disclosed is the first fluorescent probe that senses the cell surface-bound enzyme, which, furthermore, is capable of ratiometric as well as two-photon imaging with desirable features. Ratiometric imaging of cancer cell lines reveals a 6.4-8.4-fold higher GGT levels than those in normal cell lines. A comparison of the enzyme activity in organ tissues of normal and tumor xenograft mice reveals notably different levels of enzyme activity depending on the kind of tissue. Normal tissues exhibited comparable levels of enzyme activity, except the kidney that has significantly higher GGT activity (2.7-4.0-fold) than the other organs. Compared with the normal tissues, considerably higher enzyme activity was observed in the tumor tissues of the thigh (4.0-fold), colon (2.5-fold), lung (3.6-fold), and liver (2.1-fold), but essentially no enhanced activity in the tumor tissues of the spleen, stomach, and pancreas and a comparable level in both the tumor and normal kidney tissues were observed. The probe offers practical means for studying GGT-associated biology in cells and tissues by one- as well as two-photon ratiometric imaging.